The Cambridge companion to the Qurʼān - McAuliffe, Jane Dammen (Cambridge University, 2013)
As the living scriptural heritage of more than a billion people, the Qur'an speaks with a powerful voice. Nevertheless, efforts to introduce the Qur'an to English-speaking audiences have been hampered by the lack of resources. Jane McAuliffe brings together an international team of scholars to explain its complexities.